Peran Adat Alas dalam Perkembangan Kaum Muda di Aceh Tenggara - Reh Ulina Bintang; Muhammad Adika Nugraha; Abdul Azis (Medan Resource Center, 2024)
The role of Alas customs in Southeast Aceh's youth development is exemplified through the tradition of